Anjing sebagai Tamtsil al-Qur’an dalam Tafsir al-Mishbah Karya M. Quraish Shihab - Rendy Darmawan Rachmadi; Risman Bustamam; Akhyar Hanif (IAIN Batusangkar, 2023)
This study aims to reveal the amtsal about dogs in the Qur'an through the character thematic interpretation method, namely to reveal the interpretation of M. Quraish Shihab about dogs as a tamtsil of the Qur'an in surah al-'Araf verses 176–177 in the Book of Tafsir al-Mishbah. This study found that M. Quraish Shihab used the Tafsir tahlili method. As for the style of tafsir used, namely that is tafsir 'ilmi and adabi ijtima’I, meanwhile the editorial of amtsal contained in the verse is amtsal musharrahah, or a clear amtsal. M. Quraish Shihab interprets that Allah SWT gives the parable of a person who denies the verses of Allah SWT with a dog that always sticks out its tongue, due to the similarity of conditions between dogs and people who always tend to the world and follow their desires.